Indentation tests on additively manufactured metallic parts - Wimalasire, Kashan (Nanyang Technological University, 2020)
The purpose of this research is to examine the correlation of the tensile and hardness properties of stainless steel 316L (SS316L) parts made through selective laser melting (SLM) method. Qualification of additively manufactured (AM) parts is often seen as the biggest hurdle for load bearing structural components built by AM. Indentation tests have been used as a quick, economical, and non-destructive way of measuring the tensile strength of a metal alloy and thus, can play an important part in the future qualification of AM made parts. Tensile, micro-hardness and nano-indentation test were performed on SS316L dog-bone specimens, made through conventional and AM means, to obtain key mechanical properties for this study such as yield strength and hardness. The experimental findings indicate that the AM SS316L yield strength is 66% greater than that of conventional (conv.) SS316L. In addition, AM SS316L Vickers hardness 56% greater than that of conv. SS316L. Even though AM SS316L did not display any work hardening or brittle characteristics, the empirical relationship Hv ≈ 3 x does not apply as the ratio Hv/ , for AM. SS316L is 4.865, hence indentation techniques may not be viable.